Tingkat Kedisiplinan Pegawai Negeri Sipil di Kabupaten Deli Serdang Berdasarkan Peraturan Pemerintah Nomor 94 Tahun 2021 - Azzahra, Mutia Izmi; Khairiah, Nalil (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Civil Servant Discipline according to Government Regulation Number 94 of 2021 is the ability of Civil Servants to comply with obligations and avoid prohibitions specified in statutory regulations. This research aims to determine the implementation of Government Regulation Policy Number 94 of 2021 concerning Civil Servant Discipline in Deli Serdang Regency. The research method used in this research is qualitative research with a descriptive approach. This research took five sources as sources. Meanwhile, the data collection technique used in this research is interviews. The results of this research indicate that the effectiveness of implementing employee discipline policies has been carried out well, because leaders and employees are able to achieve goals and targets, implement operations, carry out regular supervision and assessments. Apart from that, the implementation of this policy is carried out intensively through briefing programs, outreach, or regular meetings so that employees can understand and comply with employee discipline policies. Through a series of training, education, policy implementation, strict supervision and evaluations that have been carried out, employees are now more disciplined in carrying out their duties. Absenteeism rates decrease, and regulatory compliance increases. Employees are expected to be consistent in completing tasks on time so that they can manage documents or correspondence well and provide the best service to the community.